Analisis Faktor-Faktor Yang Berhubungan Dengan Kejadian Hidronefrosis Di Rumah Sakit Airan Raya : Analysis of Factors Related to the Incidence of Hydronephrosis at Airan Raya Hospital - Jannah, Roudatul (Dohara POAJ, 2025)
Introduction: Hydronephrosis is a congenital abnormality that can cause acute kidney injury (AKI) and tubular damage, which can be evaluated by biomarkers, Neutrophil gelatinase-associated lipocalin (NGAL) and γ-glutathione in urine. Increasing the degree of hydronephrosis increases the risk of serious complications such as fever. The causes of hydronephrosis are classified as intrinsic compression (eg, kidney stones, ureteral stricture) and extrinsic compression (eg, prostate enlargement, pregnancy). The research objective was to determine the Analysis of Factors Related to the Incidence of Hydronephrosis at the Airan Raya Hospital in 2024. Methods: The research type is quantitative, the design used in the study uses the Cross-Sectional approach method. The population in this study were 120 patients with post-operative urethroscopic lithotripsy in the last month, based on a sample calculation of 93 respondents. The instrument used was observation with data analysis of this study using the Regression test. Results: The study results showed a p-value with the presence of kidney stones (p-value 0,000); prostate size (p-value 0,001); and urethral stricture size (p-value 0,002). Discussion: There was a significant correlation between the degree of hydronephrosis and the low p-value in these three studies suggests that there is a positive correlation between hydronephrosis and disorders including kidney stones, prostate enlargement and urethral stricture.